Enhanced methylene blue removal from aqueous solution by electrocoagulation technique using combined iron and copper electrode - Fajar , Mutiara; Agnesia , Sherly; Awan , Fajriharish Nur (Greensusmater, 2024)
The rapid advancement in the industrial sector, particularly within the textile industry, necessitates the use of colorants for fabric processing, with methylene blue being a predominant choice. However, the improper disposal of methylene blue dyes can lead to significant environmental hazards, underscoring the need for effective treatment methods before release into ecosystems. This study explores electrocoagulation, an innovative treatment technique powered by electrical energy, as a potential solution for mitigating the environmental impact of methylene blue in textile wastewater. The research investigates the efficiency of the electrocoagulation process using iron (Fe) and copper (Cu) electrodes under various operational conditions, including electrode spacing (1, 1.5, and 2 cm), applied voltage (15, 20, and 24 volts), and electrode contact time (5, 10, 15, 20, 30, and 60 minutes). The findings reveal that the electrocoagulation method achieves an optimal methylene blue removal efficiency of 99% under specific conditions: an electrode distance of 1.5 cm, an applied voltage of 24 volts, and a contact duration of 30 minutes. This research underscores the potential of electrocoagulation as an efficient and environmentally friendly approach for the treatment of textile wastewater, contributing to the sustainable management of industrial effluents.